Activity of Type I Methanotrophs Dominates under High Methane Concentration: Methanotrophic Activity in Slurry Surface Crusts as Influenced by Methane, Oxygen, and Inorganic Nitrogen. Issue 4 (1st July 2017) - Duan, Yun‐Feng; Reinsch, Sabine; Ambus, Per; Elsgaard, Lars; Petersen, Søren O.
Abstract : Livestock slurry is a major source of atmospheric methane (CH4 ), but surface crusts harboring methane‐oxidizing bacteria (MOB) could mediate against CH4 emissions. This study examined conditions for CH4 oxidation by in situ measurements of oxygen (O2 ) and nitrous oxide (N2 O), as a proxy for inorganic N transformations, in intact crusts using microsensors. This was combined with laboratory incubations of crust material to investigate the effects of O2, CH4, and inorganic N on CH4 oxidation, using 13 CH4 to trace C incorporation into lipids of MOB. Oxygen penetration into the crust was 2 to 14 mm, confining the potential for aerobic CH4 oxidation to a shallow layer. Nitrous oxide accumulated within or below the zone of O2 depletion. With 10 2 ppmv CH4 there was no O2 limitation on CH4 oxidation at O2 concentrations as low as 2%, whereas CH4 oxidation at 10 4 ppmv CH4 was reduced at ≤5% O2 . As hypothesized, CH4 oxidation was in general inhibited by inorganic N, especially NO2 –, and there was an interaction between N inhibition and O2 limitation at 10 2 ppmv CH4, as indicated by consistently stronger inhibition of CH4 oxidation by NH4 + and NO3 – at 3% compared with 20% O2 . Recovery of 13 C in phospholipid fatty acids suggested that both Type I and Type II MOB were active, with Type I dominating high‐concentration CH4 oxidation. Given the structural heterogeneity of crusts, CH4 oxidation activity likely varies spatially as constrained by the combined effects of CH4, O2, and inorganic N availability in microsites. Core Ideas: Oxygen penetration into surface crusts is shallow. Nitrous oxide accumulates at oxic–anoxic interfaces in surface crusts. Oxygen availability is important to high‐concentration CH4 oxidation. Microbial CH4 oxidation is affected by interactions of inorganic N and O2 . Activity of Type I methanotrophs dominates under high CH4 concentration.